STRATEGI OPTIMALISASI FUNGSI RUANG TERBUKA HIJAU PUBLIK MENGGUNAKAN ANALISIS SWOT DI KOTA PEKANBARU - Rezalia Eka Putri; Suwondo Suwondo; Nofrizal Nofrizal (Jurnal Ilmu Lingkungan, 2019)
Urban development currently tends to improve green open space and increase concrete construction. The Office of Public Works and Coverage reports that the new public open green space announced in 2018 is only 2.52% after increasing from 2017 which was only 1.93%. Pekanbaru City Judicial Team continues to make efforts to curb the peddlers because there are directives for street vendors to no longer be active in the Green City Pekanbaru. The purpose of this study is to analyze the evaluation of ecological, social and economic functions and issue recommendations for strategies to optimize the function of the green open space of the central city of Pekanbaru. The analytical method used is descriptive method and completed with a SWOT analysis to formulate a strategy for optimizing the function of public green space in the City Center of Pekanbaru. The recommended strategies based on the results of the SWOT analysis are (1) Addition of vegetation type composition in each public open green space in Pekanbaru City Center, (2) Reduce pavement area (cementation) and increase air infiltration areas by using paving blocks, (3) Optimize green open space facilities not maximally utilized, and (4) Confirmation of street trade policy and trade management of trademarks around Pekanbaru City Public Centers.